P5.057 Do You GYT? Evaluation of the First Two Years of the United States' National Get Yourself Tested Campaign. (13th July 2013) - Friedman, A; Habel, M; Kachur, R; Brookmeyer, K; McFarlane, M; Hogben, M; Mishel, M; Levine, S; Vadnai, L; Kantor, L
Abstract : Background: The National Get Yourself Tested (GYT) Campaign was launched in 2009 to promote STD communication and testing among youth (≤ 25 years) through multimedia platforms, on-the-ground outreach, and linking youth to free/low-cost STD testing. It is a public-private partnership effort between the U.S. Centers for Disease Control and Prevention (CDC), MTV Networks (MTV), the Henry J. Kaiser Family Foundation, and Planned Parenthood Federation of America, among other partners. This effort sought to evaluate campaign exposure and associations with STD testing and communication among youth during the first two years of implementation. Methods: Media metrics tracked campaign-related television, web and social-media programmes in 2009–10; a national mail-panel consumer survey of youth assessed campaign recall and self-reported changes in STD testing and discussions in 2010; and STD patient data from partner health centres (n = 9 affiliate health centres) tracked STD testing in April 2008 (pre-campaign), 2009 and 2010. Results: In its first two years, GYT received > 18 hours of airtime on MTV; its website received > 1.5 million views, and its testing locator made nearly 145, 000 clinic referrals. Awareness of GYT among teenage respondents (n = 766) on a national survey was 18.3%, among whom roughly 1/5 reported having talked about STDs/testing with a family member (17.5%) or friend (21.2%). Among participating affiliates, there was a 71.0% increase in patients receiving STD testing in April 2010, compared to April 2008 (at a period when chlamydia testing rates nationally rose by < 10%). Increases were most notable among young, low income and minority patients. Conclusion: This data offers encouraging evidence that GYT is reaching and mobilising youth most in need of testing. Reported testing increases in GYT-partner health centres were greater than national-level trends which varied minimally from 2008–2010. Efforts are underway to conduct a national evaluation of the campaign.